Business and Compliance Audit with Mandatory Disclosure level During the Convergence of International Accounting Standards in Brazil - Maia, Henrique Araujo; Formigoni, Henrique; da Silva, Adilson Aderito (Review of Business Management, 2012)
The aim of this study was to establish the variables that influence the level of minimal disclosure of open Brazilian companies during the initial period of harmonization with international accounting standards in Brazil. Under the methodological aspect, the study is qualitative-quantitative, of a descriptive type. The target population included non-financial Brazilian companies that are listed on Bovespa’s IBRX index. The final sample consisted of 78 companies. Data were obtained from the financial statements and notes issued by the companies in 2008 and 2009 through the Economática database and the CVM website. We used a minimal disclosure index that was made up of 72 items related to pronouncements and technical guidelines issued by the Accounting Pronouncements Committee (APC) to define the level of minimal disclosure of each sample company. Qualitative data was processed by means of a content and quantitative analysis using the Exploratory Factor Analysis (EFA) technique and the Generalized Linear Models (GLM) technique. The main results show that the size of audit firms, internationalization, the level of corporate governance and the debt levels influence significantly the level of minimal disclosure of the companies. That finding suggests that public companies of the sample audited by the big four feature better quality in the disclosure of accounting information that those companies audited by other independent audit firms. Key words: Accounting harmonization. External audit. Accounting information. Disclosure.